Unger's Bible handbook : an essential guide to understanding the Bible - Unger, Merrill F. 1909-1980 (Moody Press, 1966)
This book is a concise commentary on the entire Bible, the Bible and archaeology, historical background between the Testaments, how the Bible came to us, church history, religions of the world, with diagrams, charts, illustrations, and maps. - Publisher.